Sociocultural Variables Influencing Female Pupils’ School Dropout in the Asante Akim South Municipality of Ghana - Senyametor, Felix; Agyei, Anane; Minadzi, Vincent Mensah; Andzie, Tahir Ahmed (European Scientific Journal, ESJ, 2021)
Educating the girl-child has witnessed an elevated influence of women in education, politics, health, industry and sports among others. Advancing girls’ education is probably the most cost-effective measure for an evolving country like Ghana and other nations to enrich womanhood. Sadly, the girls’ education in Ghana appears to be on a downward trend due to their high school dropout rate. This study therefore investigated sociocultural factors influencing female school dropout -in the Asante Akim South Municipality of the Ashanti Region of Ghana. The descriptive design was employed for the study. A sample of 96, made up of 40 teachers and 56 female school dropouts was purposely selected out of a population of 3,543 from 10 public Junior High Schools. The questionnaire and structured interview were used for data collection. The results showed that some teachers’ negative attitudes, persistent teacher and peer sexual harassment of female students, teenage pregnancy and some cultural practices among others were causes of female school dropout. It was recommended that regular workshops be organized by the Ghana Education Service for Junior High School (JHS) teachers on how to professionally handle the girl-child in schools in the Asante Akim South Municipality to enable the girls stay in school thereby reducing their dropout.